PENGUJIAN SOFTWARE TESTING SISTEM ERP PT XYZ DENGAN METODE BLACK BOX TESTING - Hernanda Putri, Shalsa Abhiel; Prasetiya, Hendro Poerbo (Universitas Ma Chung, 2023)
PT XYZ is a company engaged in heavy equipment distribution. In conducting its business activities, PT XYZ requires a business management application that facilitates integrated business management, commonly known as an ERP (Enterprise Resource Planning) system. PT XYZ uses Oracle NetSuite software services for its ERP system implementation. After implementing the ERP system software, a testing phase is necessary. Since there is no documentation and integrated software testing for the ERP system at PT XYZ, the researchers will create a testing document for the ERP system software using the blackbox method, which only tests the appearance and functionality of the ERP system software. The techniques used are Equivalence Partitioning and Boundary Value Analysis.